2013
DOI: 10.1158/0008-5472.can-12-4183
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Postsurgical Advanced Metastatic Breast Cancer More Accurately Replicates the Clinical Efficacy of Antiangiogenic Drugs

Abstract: The failure rate of randomized phase III oncology clinical trials is extremely high, even when preceded by encouraging preclinical studies and phase II trial results of the same therapy. Thus there is considerable effort being made to improve the predictive clinical potential of preclinical models, in addition to improving phase II trial design. With respect to the former, preclinical models have historically relied heavily on treatment of primary spontaneous or transplanted tumors rather than the more common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 27 publications
4
84
4
Order By: Relevance
“…As we reported in previous studies, improved therapeutic outcomes, such as increase in survival or inhibition of tumor growth, observed in primary tumor studies, do not necessarily predict or correlate with the efficacy of the same drug or therapy in postsurgical metastatic studies (43,44). In this regard, the clinical analyses of the impact of antiangiogenic drugs have virtually all involved patients with early-or late-stage metastatic disease (34,35) We therefore assessed the impact of DC101 plus paclitaxel in an adjuvant treatment model, where therapy was started soon after primary tumors were resected.…”
Section: Impact Of Dc101 Combined With Chemotherapy In the Adjuvant Smentioning
confidence: 66%
“…As we reported in previous studies, improved therapeutic outcomes, such as increase in survival or inhibition of tumor growth, observed in primary tumor studies, do not necessarily predict or correlate with the efficacy of the same drug or therapy in postsurgical metastatic studies (43,44). In this regard, the clinical analyses of the impact of antiangiogenic drugs have virtually all involved patients with early-or late-stage metastatic disease (34,35) We therefore assessed the impact of DC101 plus paclitaxel in an adjuvant treatment model, where therapy was started soon after primary tumors were resected.…”
Section: Impact Of Dc101 Combined With Chemotherapy In the Adjuvant Smentioning
confidence: 66%
“…However, no survival benefit was seen in mice bearing spontaneous lung metastasis in which only a microscopic disease of either tumor type was observed in the lungs. Guerin and colleagues have recently shown that the antitumor activity of antiangiogenic drugs is effective in the treatment of primary tumors but was either ineffective or showed modest therapeutic benefit in a postsurgical advanced metastatic disease model (39). In addition, a recent study by Rovida and colleagues showed that the combination of various chemotherapy drugs, including doxorubicin, topotecan, and gemcitabine but not paclitaxel and cisplatin, inhibited the prometastatic effects of sunitinib (40).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the effects of anti-cancer therapies on experimental tumor growth and the response to these drugs in metastatic patients enrolled in early clinical trials may explain why about 85% of new drugs fail [189]. Mouse models have revealed meaningful disparities between the response of primary tumors and their visceral metastases to anti-cancer therapies [190,191]. In this regard, choosing pre-clinical models that accurately represent each stage of the metastatic cascade is also critical to understand basic biological mechanisms of metastasis formation as it occurs in patients [192] and to specifically target metastatic disease (Figure 3).…”
Section: Discussionmentioning
confidence: 99%